Paradoxos : inferências semânticas e implicaturas pragmáticas - Behle, Nanashara Fagundes (2014)
This paper aims at investigating how logical paradoxes may be approached from a logical-linguistic interface. To do that, we assume the Metatheory of Interfaces, proposed by Costa (2007, 2009a, 2009b, 2013) as methodology. Therefore, we have as external interface an intersection between concepts of Logic and Linguistics and also between concepts of Semantics and Pragmatics, subareas of Linguistics, as internal interface. The object created by the external interface in this work is the inference. We studied semantic notions of entailment and presupposition; in pragmatics we studied concepts of Gricean implicatures (1975). To better understand paradoxes we make a brief history of its origins and show important paradoxes, for instance, Zeno s Paradoxes, the Liar Paradox, Russell s Paradox and some semantic paradoxes. Then, based on an interface used by Costa (2001), we show how the Barber Paradox, the Liar Paradox and the Barbershop Paradox can be seen from a linguistic approach.